Evaluation of Contributions of Total Productive Maintenance towards Manufacturing Performance Enhancement - Sharma, Vivek (My University, 2009)
The fierce pace in manufacturing technologies in the recent times accompanied with short product life-cycle, high time-to-market pressure, vulnerable JIT and lean manufacturing strategies have made it critical for manufacturing companies to adapt the proactive corporate and management strategies as well as production philosophies and processes. In the recent times, manufacturing industry has experienced unprecedented changes related to management perspectives, production and process technologies, drastic changes in customer expectations, supplier attitudes, competitive behavior besides demanding quality requirements due to global competition. These changes have greatly influenced the fundamental shift in the way organizations envision, manage and conduct their business. This calls for making drastic changes in the company’s business environment to adapt to the rapidly changing market situation for gaining significant strategic competitive advantage. The world-class competitiveness at every level calls for on-time delivery of the best quality product at the lowest possible cost. The manufacturing organizations over the period of time have tried many proactive strategies to solve the precarious situation faced due to rapid obsolescence of technologies and stiff competition, except the most important one – Machine's health. It has been well established that though health of the machine is a vital factor for achieving reliability in a manufacturing system, but unfortunately it has been highly neglected and oversimplified by the industrial entrepreneurs. The role that effective maintenance plays in cost effective manufacturing has received a greater attention with the concepts like asset management and life cycle costing of the productions assets and units gaining importance in the recent times. Total Productive Maintenance is the latest plant management tool directed at the maximization of equipment effectiveness that results in increased productivity and reduction in costs in any industrial establishment. Leading Indian industries find TPM as an effective tool in their quest for cost effective manufacturing. The underlying reason is the premium focus of TPM strategy on equipment performance that is the main spring for delivering high yield of productivity, quality, production output, safety and morale. This study looks at both the need for and actual implementation of TPM in the Indian manufacturing industry in the quest to attain world-class competitiveness and sustainability efforts. The need for implementation of TPM in Indian industries has been brought out through the presentation of TPM benefits at a bearing manufacturing company. The various aspects of TPM implementation have also been illustrated with the help of a case study.
M.E. (Production and Industrial Engineering)
Keywords: TPM; Pillar Initiatives; Manufacturing Performance Enhancements; Type of breakdowns